Environmental drivers of mesozooplankton biomass variability in the North Pacific Subtropical Gyre. Issue 12 (28th December 2016) - Valencia, Bellineth; Landry, Michael R.; Décima, Moira; Hannides, Cecelia C. S.
Abstract: The environmental drivers of zooplankton variability are poorly explored for the central subtropical Pacific, where a direct bottom‐up food‐web connection is suggested by increasing trends in primary production and mesozooplankton biomass at station ALOHA (A Long‐term Oligotrophic Habitat Assessment) over the past 20 years (1994–2013). Here we use generalized additive models (GAMs) to investigate how these trends relate to the major modes of North Pacific climate variability. A GAM based on monthly mean data explains 43% of the temporal variability in mesozooplankton biomass with significant influences from primary productivity (PP), sea surface temperature (SST), North Pacific Gyre Oscillation (NPGO), and El Niño. This result mainly reflects the seasonal plankton cycle at station ALOHA, in which increasing light and SST lead to enhanced nitrogen fixation, productivity, and zooplankton biomass during summertime. Based on annual mean data, GAMs for two variables suggest that PP and 3–4 year lagged NPGO individually account for ~40% of zooplankton variability. The full annual mean GAM explains 70% of variability of zooplankton biomass with significant influences from PP, 4 year lagged NPGO, and 4 year lagged Pacific Decadal Oscillation (PDO). The NPGO affects wind stress, sea surface height, and subtropical gyre circulation and has been linked to mideuphotic zone anomalies in salinity and PP at station ALOHA. Our study broadens the known impact of this climate mode on plankton dynamics in the North Pacific. While lagged transport effects are also evident for subtropical waters, our study highlights a strong coupling between zooplankton fluctuations and PP, which differs from the transport‐dominated climate influences that have been found for North Pacific boundary currents. Key Points: Fluctuations in primary production are the main drivers of variability of mesozooplankton biomass at station ALOHA NPGO is the main climate pattern modulating productivity at station ALOHA MEI and PDO effects on mesozooplankton biomass were weaker and less consistent